Mars, Inc. : the billionaire's club - Bova, Ben, 1932-2020 (Baen, 2013)
"How do you get to the Red Planet? Not via a benighted government program trapped in red tape. Art Thrasher knows this. He is a man with a driving vision: send humans to Mars. Thrasher has a plan. Form a 'club' of billionaires to chip in one billion a year until the dream is accomplished. A billionaire himself and the president of a successful company, it will take all his wiles and master manipulator of business and capital to overcome setbacks and sabotage--and get a rocket full of scientists, engineers, visionaries and dreamers on their way to the Red Planet"--